2016
DOI: 10.1016/j.bmc.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel small molecule agonist scaffold for the APJ receptor

Abstract: The apelinergic system includes a series of endogenous peptides apelin, ELABELA/TODDLER and their 7-transmembrane G-protein coupled apelin receptor (APJ, AGTRL-1, APLNR). The APJ receptor is an attractive therapeutic target because of its involvement in cardiovascular diseases and potentially other disorders including liver fibrosis, obesity, diabetes, and neuroprotection. To date, pharmacological characterization of the APJ receptor has been limited due to the lack of small molecule functional agonists or ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Several series of small molecule apelin agonists that share some structural similarity to CMF-019 were recently reported by Amgen (Chen et al, 2017), Bristol-Myers Squibb (Myers et al, 2017), RTI International (Narayanan et al, 2016), and Sanford-Burnham (Pinkerton and Smith, 2015). They all possess two hydrophobic substituents extending from a heterocyclic core, reminiscent of the Sanofi series of compounds from which CMF-019 is derived (Hachtel et al, 2014; Fig.…”
Section: Synthetic Agonistsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several series of small molecule apelin agonists that share some structural similarity to CMF-019 were recently reported by Amgen (Chen et al, 2017), Bristol-Myers Squibb (Myers et al, 2017), RTI International (Narayanan et al, 2016), and Sanford-Burnham (Pinkerton and Smith, 2015). They all possess two hydrophobic substituents extending from a heterocyclic core, reminiscent of the Sanofi series of compounds from which CMF-019 is derived (Hachtel et al, 2014; Fig.…”
Section: Synthetic Agonistsmentioning
confidence: 96%
“…Recently, several studies and patents have reported the development of more suitable drug-like small molecules. Narayanan et al, (2016) used a drug library of approximately 100 compounds screened in a high-throughput Ca 2+ mobilization assay and identified four compounds based on the same structural scaffold that they designated compound 1. By experimenting with three key side chain sites, they explored the changes that were tolerated by the scaffold and suggested that this could act as a starting point for the production of more suitable drug-like small molecules.…”
Section: Synthetic Agonistsmentioning
confidence: 99%
“…A primary calcium mobilization assay and a secondary radioligand binding assay and focused screening A drug-like small molecule agonist Narayanan et al (2016) 2008), apelin-12 C3 (Hamada et al, 2008), and apelin-12 C4 (S. Huang et al, 2016). Maguire et al (2009) tested the hypothesis that apelins have vascular and cardiac actions in human tissues in vitro and compared responses with [Pyr1]apelin-13, apelin-13, and apelin-36 for the first time.…”
Section: Compound 22 C29h32n3o5fmentioning
confidence: 99%
“…ML221,w hich was described as an ApelinR functional antagonist with regardt oc AMP production and b-arrestin recruitment. [19] Small-molecule agonists werea lso reported, such as ap yrazole [20] and triazole [21] series with sub-micromolare fficacy and affinity for the ApelinR,a nd CMF-019,w hich wasr eported as the first biaseds mall-molecule apelin agonist towardGprotein signaling over b-arrestin recruitment. [22] To accelerate the discovery of other potent small-molecule agonists, it is important to develop innovative assayst hat are readily amenable to high-throughput screening (HTS).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, by using a β‐arrestin‐based functional assay, a high‐throughput screen of the NIH small molecule collection (330 600 compounds) led to the identification of ML221, which was described as an ApelinR functional antagonist with regard to cAMP production and β‐arrestin recruitment . Small‐molecule agonists were also reported, such as a pyrazole and triazole series with sub‐micromolar efficacy and affinity for the ApelinR, and CMF‐019, which was reported as the first biased small‐molecule apelin agonist toward G protein signaling over β‐arrestin recruitment…”
Section: Introductionmentioning
confidence: 99%